Routing Strategies in Survivable Optical Networks - Amin, Ifrah; ahmad dar, Gulzar; saini, Hrdeep singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Routing and wavelength assignment problem is one of the main problem in optical networks. The foremost problem is the routing problem after which the wavelength assignment is to be decided. In this paper we have proposed a routing strategy for optimization of the performance of the optical network in terms of blocking probability. The strategy proposed is better than the conventional algorithm in terms of blocking.Â